Effects of Self-Efficacy on Healthy Eating Depends on Normative Support: a Prospective Study of Long-Haul Truck Drivers - Hamilton, Kyra; Hagger, Martin (Springer New York LLC, 2018)
Purpose: Fruit and vegetable intake (FV) is insufficient in industrialized nations and there is excess of discretionary food choices (DC; foods high in fat, sugar, and salt). Long-haul truck drivers are considered a particularly at-risk group given the limited food choices and normatively reinforced eating habits at truck rest-stops. Self-efficacy and normative support are key determinants of eating behavior yet the processes underlying their effects on behavior are not well understood. We tested the direct and interactive effects of self-efficacy and normative support on healthy eating behaviors in long-haul truck drivers in a prospective correlational study. Method: Long-haul truck drivers (N = 82) completed an initial survey containing self-report measures of behavioral intentions, perceived normative support, and self-efficacy for their FV and DC behaviors. Participants completed a follow-up survey 1 week later in which they self-reported their FV and DC behavior. Results: A mediated moderation analysis identified an interactive effect of self-efficacy and normative support on behavior mediated by intention for FV and DC behavior. Specifically, we confirmed a compensation effect in which self-efficacy was more likely to have an effect on FV and DC behavior through intentions in participants with low normative support. Conclusion: Results indicate the importance of self-efficacy in predicting FV and DC intentions and behavior in the absence of a supportive normative environment. The compensatory effect of self-efficacy beliefs on behavior through intentions when normative support is low should be confirmed using experimental methods. © 2017 International Society of Behavioral Medicine